Innovative and Creative Arabic Language Learning Models in Madrasah Aliyah: A Descriptive Qualitative Study - Isop Syafei; Muhammad Oleh Solehudin; Hanifa Hanifa (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to identify the forms and characteristics of innovative and creative Arabic language learning models implemented at Madrasah Aliyah, the factors that support and hinder their application, and the impact of these innovative models on students’ motivation and engagement in the learning process. This research employs a descriptive qualitative approach to provide an in-depth portrayal of Arabic language learning innovations in Madrasah Aliyah. Data were obtained from teachers, students, school principals, and documents through observations, interviews, and documentation. The analysis followed the Miles and Huberman model, data reduction, data display, and verification. Validity was ensured through triangulation, allowing the processes, contexts, and dynamics of learning to be understood comprehensively. The findings show that innovation in Arabic language learning at Madrasah Aliyah reflects a transformation from traditional methods toward collaborative, contextual, and technology-based learning. These innovations appear in project-based learning, digital learning activities, and socio-cultural contextualization. Their success is influenced by teacher competence, student motivation, institutional support, and technological facilities. The innovative models enhance students’ motivation, engagement, and confidence in using Arabic, while reinforcing a student-centered learning paradigm that is adaptive to 21st-century competencies.